2010
DOI: 10.1080/10640266.2011.533601
|View full text |Cite
|
Sign up to set email alerts
|

A Mindful Eating Group as an Adjunct to Individual Treatment for Eating Disorders: A Pilot Study

Abstract: The objective of this study was to investigate potential benefits of a Mindful Eating Group as an adjunct to long-term treatment for a variety of eating disorders. Individuals (N = 33) attending treatment at an outpatient treatment facility participated in the 10-week intervention designed to enhance awareness around hunger and satiety cues. Disordered eating symptoms were assessed pre- and post-intervention using the EAT-26. Significant reductions were found on all subscales of the EAT-26 with large effect si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 13 publications
2
31
0
4
Order By: Relevance
“…Pre-and post-group Eating Attitude Test-26 (EAT-26) scores, which evaluated dieting, food preoccupation and oral control, revealed statistically significant reductions in these domains (Hepworth, 2011). Results are indicative of the benefits of a mindfulness-based eating awareness group as an adjunct to outpatient treatment with patients presenting with varying ED symptomatology (Hepworth, 2011). However, past research has indicated that aspects of psychological well-being, such as quality of life (QOL) may be a better indicator of change than the evaluation of physiological constructs, such as those encompassed by EAT-26 (Hepworth & Paxton, submitted).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Pre-and post-group Eating Attitude Test-26 (EAT-26) scores, which evaluated dieting, food preoccupation and oral control, revealed statistically significant reductions in these domains (Hepworth, 2011). Results are indicative of the benefits of a mindfulness-based eating awareness group as an adjunct to outpatient treatment with patients presenting with varying ED symptomatology (Hepworth, 2011). However, past research has indicated that aspects of psychological well-being, such as quality of life (QOL) may be a better indicator of change than the evaluation of physiological constructs, such as those encompassed by EAT-26 (Hepworth & Paxton, submitted).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the use of an alternate measurement tool is warranted in future studies. In addition, with previous research citing the effectiveness of mindfulness in enhancing emotional regulation (Baer et al, 2005;Smith, Shelley, Leahigh, & Vanleit, 2006), Hepworth (2011) chose a different focus, which aimed to improve the recognition of hunger and satiety cues, and use of mindfulness surrounding the relationship between food and feelings. Hepworth (2011) proposed that future studies continue to place emphasis on such topics.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations